2021
DOI: 10.1007/s13300-021-01034-w
|View full text |Cite
|
Sign up to set email alerts
|

Once-Daily Oral Semaglutide Versus Injectable GLP-1 RAs in People with Type 2 Diabetes Inadequately Controlled on Basal Insulin: Systematic Review and Network Meta-analysis

Abstract: Introduction The relative efficacy and safety of once-daily oral semaglutide vs. injectable glucagon-like peptide-1 receptor agonists (GLP-1 RAs) in subjects with type 2 diabetes (T2D) inadequately controlled on basal insulin were assessed using network meta-analysis (NMA). Methods A systematic literature review (SLR) was performed to identify randomised controlled trials of GLP-1 RAs in this population. Data at 26 ± 4 weeks were extracted for efficacy and safety outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…A systematic literature review used a network meta-analysis tool to calculate the relative efficacy and safety of once-daily oral semaglutide 14 mg versus dulaglutide 1.5 mg, twice-daily exenatide 10 μg, once-weekly exenatide 2 mg, once-daily liraglutide 1.8 mg, once-daily lixisenatide 20 μg, and once-weekly injectable semaglutide 0.5 and 1.0 mg (all GLP-1 RA class drugs) using seven clinical trials [ 50 ]. The results showed that oral semaglutide significantly reduced HbA1c levels if compared with dulaglutide (− 0.85%, 95% CI − 1.25 to − 0.45), exenatide [− 0.93%, 95% CI − 1.32 to − 0.54 (dose 10 μg) and − 0.89%, 95% CI − 1.27 to − 0.51 (dose 2 mg)], liraglutide (− 0.42%, 95% CI − 0.78 to − 0.05), and lixisenatide (− 1.32%, 95% CI − 1.74 to − 0.91) [ 50 ]. However, reductions in HbA1c were similar for oral and injectable semaglutide [− 0.32%, 95% CI − 0.72 to 0.08 (dose 0.5 mg) and 0.08%, 95% CI − 0.32 to 0.47 (dose 1.0 mg)] [ 50 ].…”
Section: Oral Semaglutide Beyond Glycemic Controlmentioning
confidence: 99%
See 4 more Smart Citations
“…A systematic literature review used a network meta-analysis tool to calculate the relative efficacy and safety of once-daily oral semaglutide 14 mg versus dulaglutide 1.5 mg, twice-daily exenatide 10 μg, once-weekly exenatide 2 mg, once-daily liraglutide 1.8 mg, once-daily lixisenatide 20 μg, and once-weekly injectable semaglutide 0.5 and 1.0 mg (all GLP-1 RA class drugs) using seven clinical trials [ 50 ]. The results showed that oral semaglutide significantly reduced HbA1c levels if compared with dulaglutide (− 0.85%, 95% CI − 1.25 to − 0.45), exenatide [− 0.93%, 95% CI − 1.32 to − 0.54 (dose 10 μg) and − 0.89%, 95% CI − 1.27 to − 0.51 (dose 2 mg)], liraglutide (− 0.42%, 95% CI − 0.78 to − 0.05), and lixisenatide (− 1.32%, 95% CI − 1.74 to − 0.91) [ 50 ]. However, reductions in HbA1c were similar for oral and injectable semaglutide [− 0.32%, 95% CI − 0.72 to 0.08 (dose 0.5 mg) and 0.08%, 95% CI − 0.32 to 0.47 (dose 1.0 mg)] [ 50 ].…”
Section: Oral Semaglutide Beyond Glycemic Controlmentioning
confidence: 99%
“…The results showed that oral semaglutide significantly reduced HbA1c levels if compared with dulaglutide (− 0.85%, 95% CI − 1.25 to − 0.45), exenatide [− 0.93%, 95% CI − 1.32 to − 0.54 (dose 10 μg) and − 0.89%, 95% CI − 1.27 to − 0.51 (dose 2 mg)], liraglutide (− 0.42%, 95% CI − 0.78 to − 0.05), and lixisenatide (− 1.32%, 95% CI − 1.74 to − 0.91) [ 50 ]. However, reductions in HbA1c were similar for oral and injectable semaglutide [− 0.32%, 95% CI − 0.72 to 0.08 (dose 0.5 mg) and 0.08%, 95% CI − 0.32 to 0.47 (dose 1.0 mg)] [ 50 ]. Oral semaglutide also significantly reduced weight compared to exenatide 2 mg (− 2.21 kg, 95% CI − 3.45 to − 0.92) and lixisenatide (− 2.39 kg, 95% CI − 3.66 to − 1.14) [ 50 ].…”
Section: Oral Semaglutide Beyond Glycemic Controlmentioning
confidence: 99%
See 3 more Smart Citations